DELUSION OF POWER-KNOWLEDGE: THE USE OF SACRED TEXTS FOR RELIGIOUS POLITICIZATION IN INDONESIA - Amrullah, Moh. Adib; Hidayatullah, Muhammad Yunus (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This paper explores the phenomenon of politicization of religion in Indonesia with a focus on the use of sacred texts as a tool to strengthen power. In this context, the concept of "power-knowledge" is studied to understand how knowledge, especially related to sacred texts, is used as an instrument to achieve political goals. Using the theoretical lens of Michel Foucault, it is interesting to highlight how political leaders use tendentious interpretations of sacred texts to manipulate public opinion, shape religious perceptions, and gain political support. Particular focus is given to the scope of Indonesia, where the politicization of religion has become an important part of the political landscape. Through in-depth analysis of case studies, this paper discusses the impact of the politicization of religion on social stability, human rights, and religious freedom in Indonesia. By delving deeper into the relationship between power and knowledge in the context of religion using library research, this paper aims to provide insights into how the use of sacred texts can shape political dynamics in Indonesia.